Protection of Victims of Fraud Crime in Victimological Studies - Fortuna, Isabella Dewi (Universitas Negeri Semarang, 2018)
Criminal acts will certainly cause the party to feel the suffering and the party is the victim. It should be remembered that victims themselves have rights that must be protected and fulfilled, the presence of the law as a legal umbrella which certainly helps in protecting and fulfilling the victim's property rights, Indonesia's own positive law has regulated the protection of victims and a discipline that also plays a role in protecting the victims. Victimology's rights are Victimology, where victimology will understand more about the victim as a result of a crime to ensure that the victim can get their rights and recompense commensurate with what the victim suffered. Crimes that occur in Indonesia are of various kinds, from murder, theft, to fraud with various modus operandi which will greatly arouse the desire of the victim to follow what the victim asks so that he is aware that he has been deceived.